A case series on conservative management in pregnancies with abnormal placentation in obstetrics: placenta accrete, increta and percreta - Tasneem, Fasiha; Shanbhag, Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Adherent placenta is one of the important causes of post- partum hemorrhage. Placenta accreta-related pathologies are an increasing contributor to maternal death from hemorrhage. With the rising caesarean delivery rate the incidence of placenta accreta has significantly increased. Morbidly adherent placenta (MAP) occurs when there is a defect in the decidua basalis, resulting in an abnormal invasion of the placenta into the substance of the uterus. A multidisciplinary approach is relevant in managing these patients in order to reduce morbidity and mortality associated with morbidly adherent placenta. A non-surgical conservative method is to leave the placenta in situ to reabsorb and institute treatment with chemotherapeutic agents, such as methotrexate. With improvement in the medical services conservative management for adherent placenta has gained significance.